Selenium: Its Role in Livestock Health and Productivity - Khanal, Dol Raj; Knight, Anthony P. (Journal of Agriculture and Environment, 2010)
Selenium (Se) is an essential metalloid trace element that has a very narrow margin of safety between the toxic and deficient doses in animals and humans. This paper highlights about the beneficial and harmful effects of Se in livestock productivity and health besides presenting some information on its relation to Khari disease of buffaloes in Baitadi and Darchula districts and ways to mitigate toxic effects of Se in buffaloes. Key words: Selenium; Deficiency; Toxicity; Khari disease The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 101-106 Uploaded date: 16 September, 2010